Is a high calcific burden an indication, or a contraindication for Drug Coated Balloon? - Sandeep Basavarajaiah; Bhagya Harindi Loku Waduge; Richard Watkin; Sampath Athukorala (Reviews in Cardiovascular Medicine, 2021)
Drug coated balloons (DCB) are increasingly being used in coronary intervention. Most of their use is currently restricted to in stent restenosis, however, they are also being used to treat some de novo lesion subsets (especially small vessels) and in patients unable to take dual antiplatelet therapy beyond a month. Calcified lesions pose a significant challenge to coronary intervention from lesion preparation to the delivery of drug to the vessel wall. There are limited data on the use of DCB in calcified lesions. In this article, we have provided a detailed literature review on calcified lesions and the use of DCB including a case example.